Perbandingan Efektivitas CT scan dan MRI dalam Evaluasi Trauma Kepala: Comparison of the Effectiveness of CT Scan and MRI in the Evaluation of Head Trauma - Nabilah Nur Hasanah; Novia Dwi Amelia Putri; Nuzul Rizky Aulia; Siti Rohimah; Shiva Nayla Putri; Elsa Amelia Nainggolan; Tio Ayu Dor Sihite; Intan Maulina (Yayasan Cita Cendekiawan Al Khwarizmi, 2026)
Head trauma is an injury caused by impact or mechanical force to the head that causes temporary or permanent brain dysfunction. Rapid and accurate evaluation is essential for determining appropriate treatment. CT scanning is the primary modality in the initial assessment of head trauma due to its widespread availability, speed of examination, and ability to detect acute intracranial hemorrhage. Conversely, MRI provides higher soft-tissue resolution and is highly sensitive for detecting diffuse axonal injury or contusions that are not visible on CT scans. The identification stage was conducted by searching the literature using keywords such as